2010
DOI: 10.1002/jso.21442
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of pelvic chondrosarcoma involving periacetabulum

Abstract: Favorable oncological and functional outcome can be achieved in selected patients with periacetabular chondrosarcomas. The complication rates were still high; however, facing the goal of limb salvage, a certain number of complications is acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 28 publications
4
58
0
Order By: Relevance
“…Higher pathological grade is correlated with the development of distant metastasis, which also worsens the prognosis for survival, and tumor stage was identified as another important independent risk factor. Such a trend further demonstrates the importance of early diagnosis, inasmuch as detection of CS originating in the pelvis is prone to delay because the early symptoms are vague …”
Section: Discussionsupporting
confidence: 88%
“…Higher pathological grade is correlated with the development of distant metastasis, which also worsens the prognosis for survival, and tumor stage was identified as another important independent risk factor. Such a trend further demonstrates the importance of early diagnosis, inasmuch as detection of CS originating in the pelvis is prone to delay because the early symptoms are vague …”
Section: Discussionsupporting
confidence: 88%
“…The 20% infection rate in our series of patients is lower than reported rates in some series [3,4,18,26,27,36,39,41,45,46] and greater or comparable to the experience reported in other studies [1,8,12,13,19,20,29,30,38] ( Table 3). The overall infection rate in many series varied from 10% to 47% after internal hemipelvectomy [1, 3, 4, 8, 10, 12, 13, 18-20, 23, 25-27, 29, 30, 34, 36, 38-41, 45, 46], whereas it ranged from 11% to 38% in patients who had resection and endoprosthetic reconstruction [1,3,12,19,20,26,27,36,45,46]. Abudu et al [3] reported a 26% infection rate in a series of 35 patients undergoing endoprosthetic reconstruction with saddle prostheses.…”
Section: Discussionsupporting
confidence: 78%
“…With the advancement of preoperative adjuvant treatments, improvements in imaging and surgical techniques, and the development of oncologically correct limb-salvage procedures, indications for hemipelvectomy in patients with pelvic malignancies have decreased dramatically [5-7]. However, in rare and complicated cases, amputation is still an option for this patient population [8].…”
Section: Introductionmentioning
confidence: 99%